PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN YANG TERDAFTAR DI BEI PADA SEKTOR KEUANGAN (TAHUN 2018-2019) - Inka Ayu Nurhana; Muhammad Hasan Ma'ruf; Johny Subarkah (Jurnal Akuntansi dan Pajak, 2021)
This study aims to determine whether the board of commissioners, independent commissioners, managerial ownership and company size have a significant effect on the performance of companies listed on the IDX. Using quantitative methods, namely primary data obtained, tested using descriptive statistical tests based on the description of the performance of financial sector companies The research population is the parties involved in companies listed on the Stock Exchange in financial sector companies. The sample used is as many as listed companies, the total sample for 2 years is 38 companies. Research test equipment with classical assumption test includes normality, multicollinearity, heteroscedasticity and autocorrelation. The results of the study: (1) the Board of Commissioners (X1) has no significant effect on the company's performance, the t count variable X1 (0.842) is smaller than t table (2.03224) so the decision H1 is rejected. (2) independent commissioner (X2) has no significant effect on company performance, t count variable X2 (1.039) is smaller than t table (2.03224) then the decision H2 is rejected. (3) managerial ownership (X3) has no significant effect on company performance, t-count variable X3 (1,340) is smaller than t table (2,03224), so the decision H3 is rejected. (4) company size (X4) has a significant effect on company performance, t count variable X4 (3,849) is smaller than t table (2,03224) then the decision H4 is accepted.